2020
DOI: 10.3389/fcell.2020.578197
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Isorhamnetin in Human Amniotic Epithelial Stem Cells in vitro and Its Cardioprotective Effects in vivo

Abstract: Cardiac hypertrophy and fibrosis are major pathophysiologic disorders that lead to serious cardiovascular diseases (CVDs), such as heart failure and arrhythmia. It is well known that transforming growth factor β (TGFβ) signaling pathways play a major role in the proliferation of cardiac hypertrophy and fibrosis, which is mainly stimulated by angiotensin II (AgII). This study aimed to investigate the cardioprotective potential of isorhamnetin (ISO) in human amniotic epithelial stem cells (hAESCs) through global… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…In the present study, we have used hAECs that were preserved at the Tsukuba Human Tissue Biobank Center (THB). THB was established at the University of Tsukuba in November 2013 with an aim to reserve human biospecimens to promote medical research [ 56 , 57 ]. The protocol for isolation, collection, and use of hAECs and other biospecimens was approved by the Ethical Review Committee of the University of Tsukuba Hospital (approval code: H27-58, approval date: 10 July, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, we have used hAECs that were preserved at the Tsukuba Human Tissue Biobank Center (THB). THB was established at the University of Tsukuba in November 2013 with an aim to reserve human biospecimens to promote medical research [ 56 , 57 ]. The protocol for isolation, collection, and use of hAECs and other biospecimens was approved by the Ethical Review Committee of the University of Tsukuba Hospital (approval code: H27-58, approval date: 10 July, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Isorhamnetin has a protective effect on ischemia–reperfusion injury of isolated rat hearts [ 26 ]. ISO was found to reverse the enhanced TGF- β and collagen type I alpha 1 mRNA expression induced by AgII exposure, which causes cardiovascular remodeling in ventricular tissue [ 27 ]. Isorhamnetin treated myocardial-related diseases by regulating PI3K, Akt, and NF- κ B signaling pathway [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Li and colleagues revealed that isorhamnetin could also inhibit the growth of the gefitinib resistant PC9 cells (PC9-IR) by downregulating BCL-2 gene expression and PCNA protein expression, inhibiting DNA synthesis and upregulating P53 , BAX and CASP3 gene expression [ 22 ]. Along with this, Aonuma et al [ 71 ] demonstrated that isorhamnetin might efficiently suppress hypertrophy and fibrosis induced by angiotensin II in cardiac tissue by regulating transforming growth factor (TGF-β) pathways. Furthermore, it might have appreciated properties on potential clinical consequences of cardiovascular diseases by the renin-angiotensin system regulation.…”
Section: General Overview Of Biological Activities Of Isorhamnetinmentioning
confidence: 97%
“…We have established a stem cell-based tool using a perinatal stem cell, human amniotic epithelial cells (hAECs), to evaluate the bioactivities of natural compounds employing whole-genome microarray analysis [ 71 , 140 , 141 , 142 , 143 , 144 ]. In recent years, an increasingly large number of bioactive compounds of medicinal plants have been screened for their potential therapeutic and preventive effects.…”
Section: A Post Hoc Transcriptome Analysis Predicts the Potential Effect Of The Isorhamnetin On Diabetes In A Stem Cell-based Toolmentioning
confidence: 99%
See 1 more Smart Citation